The Evolution of Public Debt, Gross Domestic Product and Inflation Rate in Poland in 2015-2021 - Lipka, Aleksandra; Nowacka, Daria; Rzeszutek, Andrzej (Olsztyn Economic Journal, 2022)
The research aimed to assess the amount of public debt, GDP, and inflation in Poland and to forecast it for the period 2022-2026. The amount of public debt in the years under study, and two macroeconomic measures, GDP and inflation, were analyzed. The research was conducted based on data obtained from the Central Statistical Office, the Ministry of Finance, and Eurostat. One of the main research objectives of the study was to find a relationship between the level of GDP and public debt. To this end, vertical analysis of the acquired data was carried out and Pearson linear correlation coefficients were calculated. Another important aspect addressed in the study was the magnitude of average annual inflation rates, compared to the volume of public debt. To this end, the focus was on carrying out a vertical analysis of the variables that made it possible to find relationships between inflation and public debt. The focus was also on examining the share of public debt in GDP for Poland related to selected EU member states. The analysis was carried out in three countries each with a high and low correlation of the indicator under study. The analysis carried out allowed for the confirmation of the hypotheses put forward in this study that public debt is correlated with both GDP and the level of inflation in Poland. The estimated forecasts made it possible to conclude that the public debt will gradually increase over the next 5 years.